2012
DOI: 10.1089/lap.2012.0095
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Access to Video-Assisted Thoracic Surgical Lobectomy for Treatment of Early-Stage Lung Cancer

Abstract: For the period studied, patients in rural areas, in low-volume hospitals, who had Medicaid, or with lower median incomes underwent VATS lobectomy less often.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 12 publications
0
8
0
1
Order By: Relevance
“…In this study, we found that the VATS approach was more expensive than the open approach. Several previous reports have demonstrated that the costs of VATS lobectomy were lower than open thoracotomy because of shorter hospital stay (21)(22)(23)(24)(25)(26)(27). Most of these studies were from developed countries.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that the VATS approach was more expensive than the open approach. Several previous reports have demonstrated that the costs of VATS lobectomy were lower than open thoracotomy because of shorter hospital stay (21)(22)(23)(24)(25)(26)(27). Most of these studies were from developed countries.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the variability in access to care as measured by distance to facility or facility type and/or volume, it was notable that an urban-rural divide may play a role. Our sample has too few 4 However, previous suggestions of combining initial diagnostics locally with coordination and continuity of care at referral facilities may mitigate some of the access to care disparities revealed in our analysis. 11 Policy makers and health care system architects should continue addressing disparities in access to surgery and multimodality therapy to ensure equity of care for patients with MPM.…”
Section: Jama Network Open | Oncologymentioning
confidence: 74%
“…Similar findings related to median zip code income have been reported for surgical treatment in early-stage lung cancer. 4 Moreover, additional SDOHs, such as level of education, have yet to be evaluated systematically in MPM, although they have been identified in other thoracic tumor types, such as tracheal cancer. 5 Furthermore, although the distance to treatment is associated with survival rates in multiple reports, access to treatment for patients with MPM should be studied.…”
Section: Introductionmentioning
confidence: 99%
“…African–Americans were least likely to receive a MI approach, along with those on Medicaid or living in rural communities. This correlation has been published utilizing inpatient discharge claims data as far back as 2008, 17 and other hospital database studies have shown a link between low socioeconomic status and readmission rates 18 . Diversity, equity, and inclusion has become a focus of the major surgical societies.…”
Section: Discussionmentioning
confidence: 91%